Implication of SD-PAMs in Nigeria (Global Journal of Science Frontier Research, 2015)
Sustainable Development Policies and Measures (SD-PAMs) have been identified as a possible means through which developing nations can contribute to the global climate change mitigation and adaptation effort. Nigeria being an oil producing nation derives up to 70% of her revenue from the petroleum industry but the gas sector has not be given the necessary attention until recently resulting to both economic and environmental lost via gas flaring or what is called fugitive gas. This natural gas being flared has the potential of putting to an end the epileptic electricity situation in the country, if well harnessed and managed. Nigeria ranks second in the World in terms of total volume of gas being flared, but according to World Bank 2007 report, there was a remarkable reduction of about 10 BCM of gas flaring in Nigeria between 1996 and 2005, about the same period that Nigeria Liquified Natural Gas (NLNG) and some Independent Power Project that utilizes natural gas was commissioned. The NLNG has being a source of revenue for government and provides jobs for the teeming youth of the restive Niger-Delta area. Strong political in the form of sustainable development policies and measures will to put an end to gas flaring and well structure national gas master plan that focus on meeting local demand is still required for optimum economic and environmental gains to be achieved.
Keywords: adaptation; fugitive gas; gas flaring; mitigation; sustainable development policies and measures